Modeling and performance analysis of MWCNT bundle interconnect based on state space method - Songjie Zhao; Fang Deng (Materials Research Express)
To efficiently analyze the time-domain and frequency-domain characteristics of novel interconnects, this paper focuses on multi-walled carbon nanotube (MWCNT) bundle interconnects as the primary subject of research and proposes a state space model that is applicable to carbon nanotube interconnects, graphene nanoribbon interconnects and various improved structures. Using the state space method, the equivalent circuit model of single MWCNT bundle interconnect that primarily adopts voltage-mode signaling (VMS) and current-mode signaling (CMS) is solved, respectively. Additionally, the transient output responses and frequency responses of the interconnect at local, intermediate, and global levels for 14 nm technology node are analyzed to evaluate the delay and 3 dB bandwidth performance for different modes. And the noise peak and power dissipation are also discussed. The proposed state space method is found to be highly accurate and effective by comparing with the simulation results from the SPICE environment in ADS and ABCD parameter matrix method. Furthermore, the method presented in this paper is suitable for solving multi-line coupled interconnects and can provide some meaningful theoretical guidance for analyzing the electrical characteristics of novel interconnects.